2012
DOI: 10.1021/la203155d
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures Increase Water Droplet Adhesion on Hierarchically Rough Superhydrophobic Surfaces

Abstract: Hierarchical roughness is known to effectively reduce the liquid-solid contact area and water droplet adhesion on superhydrophobic surfaces, which can be seen for example in the combination of submicrometer and micrometer scale structures on the lotus leaf. The submicrometer scale fine structures, which are often referred to as nanostructures in the literature, have an important role in the phenomenon of superhydrophobicity and low water droplet adhesion. Although the fine structures are generally termed as na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 48 publications
4
86
0
Order By: Relevance
“…This is explained by water's ability to penetrate into the porous structure (the droplet resides partially in the Wenzel state). 14 The initial surface of the oil-infused structure displays a complete opposite behavior with a water sliding angle value of 3 , which satisfies the additional requirement for superhydrophobicity of WSA lower than 10 . This value shows an increase in the level of the plain oiled surface after the first cycle of the ice adhesion testing.…”
Section: -2mentioning
confidence: 77%
“…This is explained by water's ability to penetrate into the porous structure (the droplet resides partially in the Wenzel state). 14 The initial surface of the oil-infused structure displays a complete opposite behavior with a water sliding angle value of 3 , which satisfies the additional requirement for superhydrophobicity of WSA lower than 10 . This value shows an increase in the level of the plain oiled surface after the first cycle of the ice adhesion testing.…”
Section: -2mentioning
confidence: 77%
“…Many researchers have used the presence of hybrid states to explain particular water adhesion behaviors on surfaces with dualscale roughness, e.g., Cassie-Baxter in the microscale and Wenzel in the nanoscale, or vice versa, or a semi-Cassie-Baxter state where the liquid meniscus partially penetrates the rough features. Similarly, the water-filled Wenzel state with micro/nano structures is illustrated in Figure 2e, and the waterfilled Cassie state with nanostructures is demonstrated in Figure 2f [30][31][32][33]. …”
Section: Wetting Transitions On Rough Surfacesmentioning
confidence: 87%
“…Many researchers have used the presence of hybrid states to explain particular water adhesion behaviors on surfaces with dualscale roughness, e.g., Cassie-Baxter in the microscale and Wenzel in the nanoscale, or vice versa, or a semi-Cassie-Baxter state where the liquid meniscus partially penetrates the rough features. Similarly, the water-filled Wenzel state with micro/nano structures is illustrated in Figure 2e, and the waterfilled Cassie state with nanostructures is demonstrated in Figure 2f [30][31][32][33]. Engineering transparent surfaces that actively repel water [34], oil [35], low-surface-tension liquids [36], and/or organic liquids have many applications in the fields of fluids [37,38], chemical shielding [39], stain-proof coatings [40,41], membrane technologies [42], and antifouling coatings [43].…”
Section: Wetting Transitions On Rough Surfacesmentioning
confidence: 97%
“…The R812S silica nanoparticles and Polydimethylsiloxane (PDMS) silicone oil revealed that this complex is highly water resistant because of its unique nanostructured morphology. The efforts are being made to develop TiO 2 nanoparticles coating to provide hydrophobic property to the paper with the help of liquid flame spray technique (Teisala et al, 2012). TiO 2 and Ag nanoparticles were synthesized and coated onto a paper prepared from rice straw.…”
Section: Edible Nano Coatings and Nano Coating Materialsmentioning
confidence: 99%